Norwegian deep‐water coral reefs: cultivation and molecular analysis of planktonic microbial communities. (7th July 2014) - Jensen, Sigmund; Lynch, Michael D. J.; Ray, Jessica L.; Neufeld, Josh D.; Hovland, Martin
Summary: Deep‐sea coral reefs do not receive sunlight and depend on plankton. Little is known about the plankton composition at such reefs, even though they constitute habitats for many invertebrates and fish. We investigated plankton communities from three reefs at 260–350 m depth at hydrocarbon fields off the mid‐Norwegian coast using a combination of cultivation and small subunit (SSU) rRNA gene and transcript sequencing. Eight months incubations of a reef water sample with minimal medium, supplemented with carbon dioxide and gaseous alkanes at in situ ‐like conditions, enabled isolation of mostly A lphaproteobacteria ( S ulfitobacter, L oktanella ),   G ammaproteobacteria ( C olwellia ) and F lavobacteria ( P olaribacter ). The relative abundance of isolates in the original sample ranged from ∼ 0.01% to 0.80%. Comparisons of bacterial SSU sequences from filtered plankton of reef and non‐reef control samples indicated high abundance and metabolic activity of primarily A lphaproteobacteria (SAR11 Ia), G ammaproteobacteria (ARCTIC96BD‐19), but also of D eltaproteobacteria ( N itrospina, SAR324). Eukaryote SSU sequences indicated metabolically active microalgae and animals, including codfish, at the reef sites. The plankton community composition varied between reefs and differed between DNA and RNA assessments. Over 5000 operational taxonomic units were detected, some indicators of reef sites (e.g. F lavobacteria, C ercozoa, D emospongiae ) and some more active at reef sites (e.g. G ammaproteobacteria, C iliophora, C opepoda ).